Self-esteem in children with attention-deficit/ hyperactivity disorder - Lerdpaisanskul, Mutita; Boonchooduang, Nonglak; Charnsil, Chawanun; Louthrenoo, Orawan (Biomedical Sciences and Clinical Medicine, 2017)
Introduction Attention-de fi cit/hyperactivity disorder (ADHD) in children often manifests itself in diffi cult behaviors which may have an impact on their self-esteem. Findings from previous studies regarding self-esteem in children with ADHD are inconsistent. This study aimed to assess selfesteem in children with ADHD in comparison to healthy controls. Methods This was a cross-sectional study of children aged 8-15 years, who had been diagnosed with ADHD. Children of the same age and gender, without ADHD or chronic illnesses, were enrolled as a comparison group. Self-esteem assessment using the Five-Scale Test of Self-Esteem for Children (FSC) was completed by the children themselves. Results The study population included 130 children with a mean age of 11.05±2.21 years. Sixtyfive cases were ADHD and 65 were healthy controls. The mean FSC score in the ADHD group was signi fi cantly lower than that of the control group indicating lower self-esteem in the ADHD group (45.06±8.08 vs 49.88±8.40, p=0.001). Among the children with ADHD, variables including age, gender, scores on school report, and comorbid conditions were not associated with the total self-esteem score. However, when focusing speci fi cally on self-esteem subscales, the school report was signi fi cantly related to the academic subscale of self-esteem in children with ADHD (β 0.81, 95%CI 0.11-1.5, p=0.03). Conclusion Findings from this study have suggested that children with ADHD perceive themselves more negatively compared with healthy controls. Fostering self-esteem should be included in the comprehensive care for children with ADHD. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />